Characteristics of Mudgrovel Crabs Caught Using Trap Fishing Gear in Lambur Luar Village, Muara Sabak Timur District - Destiani, Dinda; Depison; Magwa, Rizky Janatul; Lisna; Ramadan, Fauzan; Leni, Yusyam (Aquaculture Department, University of Mataram, 2025)
Mangrove crabs are a type of crustacean that lives in mangrove and estuary ecosystems. one of the freshwater fishery products that have high economic value that are often caught in Lambur Luar Village using trap fishing gear. Purpose of this study was to describe the characteristics of mangrove crabs caught using traps in Lambur Luar Village, Jambi Province. This study was conducted from February 1-16, 2025. The research method used was a census, with data collection techniques using probability sampling. The data observed included the type of mangrove crab, weight, carapace length, carapace width, and sex. Differences in weight, length, and carapace width of mangrove crabs were analyzed using ANOVA followed by Duncan's test at a significance level of 5%. The results showed that there were three species of mangrove crabs caught, namely Scylla serrata, Scylla olivacea, and Scylla tranquebarica. After ANOVA test and Duncan's further test, it was found that the carapace length between Scylla serrata, Scylla olivacea, and Scylla tranquebarica was significantly different (p≤0.05). while the carapace width and weight were not significantly different (p>0.05). Variations sex ratio in the Scylla serrata species were (0.78:0.22) and Scylla tranquebarica (0.67:0.33), indicating that the male population was more dominant in these two species. While the Scylla olivacea species, the sex ratio was almost balanced, namely (0.51:0.49). The conclusion of this study is that the characteristics of mangrove crabs differ between males and females, and there are significant differences in carapace length between mangrove crab species found in Lambur Luar Village.